Marketing research of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology - T. P. Zarichna; T. S. Brytanova; T. S. Raikova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim of work is marketing research of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology.